2017
DOI: 10.1038/s41430-017-0013-x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inflammatory index and inflammatory biomarkers in adolescents from LabMed physical activity study

Abstract: Background/objectives The dietary inflammatory index (DII) is a tool to measure the diet's inflammatory potential and has been used with adults to predict low-grade inflammation. The present study aims to assess whether this dietary score predicts low-grade inflammation in adolescents.Subjects/methods The sample comprises 329 adolescents (55.9% girls), aged 12-18 years, from LabMed Physical Activity Study. DII score was calculated based on a food-frequency questionnaire and categorized into tertiles. We collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
5
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 47 publications
2
41
5
4
Order By: Relevance
“…Although this study found no association between DII with other cardiometabolic risk factors as we expected, other studies also did not observe such an association [20,[50][51][52][53]. Noteworthy, the mean of the DII (0.15) of our sample did not characterize a pro-inflammatory diet in general, but in the ORISCAV-LUX study conducted with 1352 people they also did not present a pro-inflammatory diet in general [20].…”
Section: Discussioncontrasting
confidence: 78%
“…Although this study found no association between DII with other cardiometabolic risk factors as we expected, other studies also did not observe such an association [20,[50][51][52][53]. Noteworthy, the mean of the DII (0.15) of our sample did not characterize a pro-inflammatory diet in general, but in the ORISCAV-LUX study conducted with 1352 people they also did not present a pro-inflammatory diet in general [20].…”
Section: Discussioncontrasting
confidence: 78%
“…The lack of association between the C-DII and IL-6 observed in this study may be due to the variability in IL-6 concentrations in our population, less sensitivity of this biomarker or due to ethnicity [57]. Results for this cytokine remain controversial in children; some studies in non-Hispanic children have also reported no associations [58] while others have reported a significant positive association [59]. Moreover, a recent study in Mexican adults found, over a period of 13 years, a positive association between the highest quartile of DII and the incidence of metabolic syndrome (HRQ4vsQ1 = 1.99; 95% CI: 1.03, 3.85; P-trend = 0.04), particularly associated with hypertriglyceridemia, hypertension and abdominal obesity [60].…”
Section: Discussioncontrasting
confidence: 58%
“…12 Furthermore, the dietary inflammatory index was previously used in Portuguese children. 23,24 Secondly, although the dietary definition. Similar to previous studies addressing the role of diet on asthma medication use, asthma medication includes both inhaled corticosteroids and short-acting bronchodilators.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unlikely that most of the children with respiratory disease differentially adopt a pro‐inflammatory dietary pattern . Furthermore, the dietary inflammatory index was previously used in Portuguese children . Secondly, although the dietary inflammatory index has been calculated using the 24‐hour recall, not accounting for daily or seasonal variability in dietary patterns, this index was designed to be used with dietary data collected from different assessment methods, including the 24‐hour recall .…”
Section: Discussionmentioning
confidence: 99%